2002
DOI: 10.1152/ajpcell.00502.2001
|View full text |Cite
|
Sign up to set email alerts
|

Apparent elastic modulus and hysteresis of skeletal muscle cells throughout differentiation

Abstract: The effect of differentiation on the transverse mechanical properties of mammalian myocytes was determined by using atomic force microscopy. The apparent elastic modulus increased from 11.5 +/- 1.3 kPa for undifferentiated myoblasts to 45.3 +/- 4.0 kPa after 8 days of differentiation (P < 0.05). The relative contribution of viscosity, as determined from the normalized hysteresis area, ranged from 0.13 +/- 0.02 to 0.21 +/- 0.03 and did not change throughout differentiation. Myosin expression correlated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
212
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(241 citation statements)
references
References 42 publications
27
212
2
Order By: Relevance
“…Although the upper cell sees only a soft cell below it, the lower cell always sees rigid substrate below it in spite of the soft cell above. The elastic modulus of earlystage myotubes has been determined previously by AFM indentation (Collinsworth et al, 2002) and proves remarkably similar to elastic moduli reported for the passive elasticity of skeletal muscle tissue. Separate studies of our own with C2C12 cells grown on collagen-coated polyacrylamide gels confirm that a tissue-like substrate modulus is indeed optimal for myotube differentiation (see Fig.…”
Section: Cell Patterning and Ridgidity-inhibited Differentiationsupporting
confidence: 84%
See 1 more Smart Citation
“…Although the upper cell sees only a soft cell below it, the lower cell always sees rigid substrate below it in spite of the soft cell above. The elastic modulus of earlystage myotubes has been determined previously by AFM indentation (Collinsworth et al, 2002) and proves remarkably similar to elastic moduli reported for the passive elasticity of skeletal muscle tissue. Separate studies of our own with C2C12 cells grown on collagen-coated polyacrylamide gels confirm that a tissue-like substrate modulus is indeed optimal for myotube differentiation (see Fig.…”
Section: Cell Patterning and Ridgidity-inhibited Differentiationsupporting
confidence: 84%
“…In addition, as these cells differentiate further with striation in classic culture conditions, they stiffen, as measured using atomic force microscopy (AFM) (Collinsworth et al, 2002). Stiffness of smooth muscle cells (measured by twisting magnetic beads) also increases linearly with contractile stress ).…”
mentioning
confidence: 99%
“…Experiments concerned changes in cell stiffness upon increasing Ca 2+ concentration [939,940] or the cellular contractility [941]. Also, the effect of cell differentiation [942], cell division [943], shear stress [917,944], culture time [307], and cell spreading [945] has been studied. Deformability of endothelial cell was found to increase after contact with monocytes (considered to play a major role in the early stage of atherosclerosis) [946].…”
Section: Filled Polyelectrolyte Capsulesmentioning
confidence: 99%
“…Recent studies reveal a previously unappreciated role for the stiffness of the ECM in regulating satellite cell proliferation and differentiation. Resting healthy skeletal muscles and cultured myotubes possess a similar elastic stiffness (elastic modulus ϳ12 kPa) (106,152), whereas aged (184,444) and dystrophic (152) skeletal muscles are apparently stiffer (elastic modulus ϳ418 kPa). These changes of stiffness are presumably due to increased extracellular matrix deposition, in particular collagen deposition by fibroblasts, a result of repeated muscle regeneration.…”
Section: Ecm and Associated Factorsmentioning
confidence: 99%